Social network: evaluation of the support or containment contexts of lesbian mothers - Firley Poliana da Silva Lúcio; Paula Daniella de Abreu; Eliane Maria Ribeiro de Vasconcelos; Ednaldo Cavalcante de Araújo (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To evaluate the social network of lesbian mothers, from the social contexts of support or restraint. Method: Descriptive, exploratory study, of qualitative approach, based on the theoretical reference of Social Network, with eight lesbian mothers selected through Snowball technique, using semi-structured interview. Data analysis was performed with IRAMUTEQ software, through Similarity Analysis. Results: The social network is configured as: 1) Emotional distance and non-acceptance of motherhood by the family members - primary network elements; 2) Interference in the socio-cultural medium for the effectiveness of the mother-child bond - secondary network elements. Final considerations: Social network is grounded on trivialized and negative conceptions that highlight prejudice and disrespect. The discussion of this theme contributes to a greater visibility of those new family arrangements as well as to reduce stigmas e prejudices that pervade the social network components of these women.